ANALISA EFISIENSI BIAYA PEMBERIAN TEPUNG BAWANG PUTIH TERHADAP PERFORMA BURUNG PUYUH PADA FASE LAYER - Husaifi Nur Wahyudi Ahmad; Rofiq Ghozali Ahmad; Moelya Moes Edya (Universitas Islam Balitar, 2018)
This aims of the study is to analysed the effects of addition garlic powder in diet of quail. Data experiment were held on 1 th August – 15 th September 2017 at Ghozali Farm, Nglegok subdistric, Blitar regency. Two hunbred fourty quail age 6 to 7 months were used in this study. A randomized completely design was applied with 4 treatments and 5 replications. The treatment consists of P0: controls, P1: 0,2% addition garlic powder, P2: 0,4% addition garlic powder and P3: 0,6% addition garlic powder.The variance observed IOFC. The conclusion based on the result were : the treatment significant on IOFC and Return Cost Ratio. Its suggested to use 0,2% addition of garlic powder on quail ration.